2019
DOI: 10.1093/ajh/hpz022
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Renin Activity Is a Predictive Biomarker of Blood Pressure Response in European but not in African Americans With Uncomplicated Hypertension

Abstract: Hypertension (HTN) is one of the most common chronic diseases, with a prevalence of 45.6% among US adults aged 20 years and older. 1 It is a primary risk factor for multiple adverse cardiovascular outcomes, including angina, myocardial infarction, heart failure, and stroke. 2 Use of antihypertensive drugs to control high blood pressure (BP), particularly high systolic BP (SBP), has been proven to reduce cardiovascular risks and prevent target organ damage. 3,4 However, recent data demonstrate that among hypert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Previous studies demonstrate that PRA is a predictive biomarker of BP response to antihypertensive agents particularly in European American hypertensive patients [ 5 , 6 , 7 , 8 ]. Patients with lower PRA (< 0.65 ng/mL/h) achieve greater BP reductions in response to thiazide diuretics than β-blockers, whereas those with higher PRA (≥ 0.65 ng/mL/h) respond better to β-blockers than thiazide diuretics [ 9 , 10 , 11 ]. However, PRA, other clinical factors and the genetic variants identified to date, including those related to PRA, only explain about 3–4% of the total variability in the BP trait [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrate that PRA is a predictive biomarker of BP response to antihypertensive agents particularly in European American hypertensive patients [ 5 , 6 , 7 , 8 ]. Patients with lower PRA (< 0.65 ng/mL/h) achieve greater BP reductions in response to thiazide diuretics than β-blockers, whereas those with higher PRA (≥ 0.65 ng/mL/h) respond better to β-blockers than thiazide diuretics [ 9 , 10 , 11 ]. However, PRA, other clinical factors and the genetic variants identified to date, including those related to PRA, only explain about 3–4% of the total variability in the BP trait [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…22 Recently, we and others demonstrated that PRA is statistically significantly associated with BP response to multiple antihypertensives and that patients-especially EAs-with higher-PRA vs. lower-PRA categories have different BP responses to antihypertensive medications. 9,10,14 Moreover, we have shown that a PRA cutoff point of 0.60 ng/mL/hr, a cutoff point originally established in a cohort of EA patients decades ago, 23 has a sensitivity of 48.3% and a specificity of 85.1% to predict the BP response to chlorthalidone vs. metoprolol in EA patients with primary uncomplicated HTN. 14 The clinical utility of PRA as a biomarker was evaluated in a prospective study of 73 resistant patients with HTN followed for 1 year.…”
Section: Discussionmentioning
confidence: 89%
“…9,10,14 Moreover, we have shown that a PRA cutoff point of 0.60 ng/mL/hr, a cutoff point originally established in a cohort of EA patients decades ago, 23 has a sensitivity of 48.3% and a specificity of 85.1% to predict the BP response to chlorthalidone vs. metoprolol in EA patients with primary uncomplicated HTN. 14 The clinical utility of PRA as a biomarker was evaluated in a prospective study of 73 resistant patients with HTN followed for 1 year. This study showed that PRA-guided antihypertensive medication selection resulted in significantly fewer antihypertensive medications required to control BP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations